2018
DOI: 10.1186/s40560-018-0278-8
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin fails to improve ARDS in patients undergoing ECMO therapy

Abstract: BackgroundAcute respiratory distress syndrome (ARDS) is associated with high mortality rates. ARDS patients suffer from severe hypoxemia, and extracorporeal membrane oxygenation (ECMO) therapy may be necessary to ensure oxygenation. ARDS has various etiologies, including trauma, ischemia-reperfusion injury or infections of various origins, and the associated immunological responses may vary. To support the immunological response in this patient collective, we used intravenous IgM immunoglobulin therapy to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Inclusion criteria included being over 18 years of age, possessing a PCR-confirmed COVID-19 diagnosis, involvement of > than 30% of both lungs (ground-glass opacity) in high-resolution computed tomography (HRCT) (confirmed by two radiologists), O 2 saturation (satO 2 ) of < 90%, and a lack of adequate response to initial treatment including at least both one antiviral and one chloroquine-class drug. Exclusion criteria, in addition to an age of less than 18 years, included pregnancy, coagulation disorders (such as hemophilia, Von Willebrand disease, other clotting factor deficiencies), history of hypersensitivity to IVIg, advanced heart failure (defined as a left ventricular ejection fraction less than 35%), pulmonary fibrosis/history of lung surgery, and the presence of either sarcoidosis or tuberculosis (that may interfere with an accurate estimation of the severity of pulmonary interference by COVID- 19).…”
Section: Study Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria included being over 18 years of age, possessing a PCR-confirmed COVID-19 diagnosis, involvement of > than 30% of both lungs (ground-glass opacity) in high-resolution computed tomography (HRCT) (confirmed by two radiologists), O 2 saturation (satO 2 ) of < 90%, and a lack of adequate response to initial treatment including at least both one antiviral and one chloroquine-class drug. Exclusion criteria, in addition to an age of less than 18 years, included pregnancy, coagulation disorders (such as hemophilia, Von Willebrand disease, other clotting factor deficiencies), history of hypersensitivity to IVIg, advanced heart failure (defined as a left ventricular ejection fraction less than 35%), pulmonary fibrosis/history of lung surgery, and the presence of either sarcoidosis or tuberculosis (that may interfere with an accurate estimation of the severity of pulmonary interference by COVID- 19).…”
Section: Study Samplementioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19) was declared to be a pandemic by the World Health Organization on March 11th, 2020 [1]. The culprit virus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is highly communicable and can spread through respiratory droplets [2].…”
Section: Introductionmentioning
confidence: 99%
“…Our results provide evidence to support the administration of IVIg for improving clinical outcomes in COVID-19 patients with severe respiratory system involvement. Prohaska et al previously conducted research to suggest that IVIg could not be used effectively to reduce the mortality of patients with the acute respiratory syndrome (ARDS) undergoing extracorporeal membrane oxygenation (ECMO) therapy [19]. In this study, patients with bacterial and/or fungal infection included 54% of patients in the IVIg treatment group and 28% of patients in the control (placebo) group [19].…”
Section: Discussionmentioning
confidence: 98%
“…Prohaska et al previously conducted research to suggest that IVIg could not be used effectively to reduce the mortality of patients with the acute respiratory syndrome (ARDS) undergoing extracorporeal membrane oxygenation (ECMO) therapy [19]. In this study, patients with bacterial and/or fungal infection included 54% of patients in the IVIg treatment group and 28% of patients in the control (placebo) group [19]. As the mechanisms under which our immune system eradicated bacterial and viral infections are not the same, the results of this study could not be generalised for those patients with a merely viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Prohaska et al showed that IVIg could not reduce the mortality of patients with ARDS undergoing extracorporeal membrane oxygenation (ECMO) therapy. In this study, patients with bacterial and fungal infection also included, and only 54% of patients in the IVIg group and 28% of patients in the control group had viral infection (13). Recently, a randomized controlled trial studied the hyperimmune IVIg (hIVIg) effect on patients with con rmed in uenza A or B infection.…”
Section: Discussionmentioning
confidence: 99%